Cardiac pacing using transmural multi-LED probes in channelrhodopsin-expressing mouse hearts. (August 2020) - Zgierski-Johnston, C.M.; Ayub, S.; Fernández, M.C.; Rog-Zielinska, E.A.; Barz, F.; Paul, O.; Kohl, P.; Ruther, P.
Abstract: Optogenetics enables cell-type specific monitoring and actuation via light-activated proteins. In cardiac research, expressing light-activated depolarising ion channels in cardiomyocytes allows optical pacing and defibrillation. Previous studies largely relied on epicardial illumination. Light penetration through the myocardium is however problematic when moving to larger animals and humans. To overcome this limitation, we assessed the utility of an implantable multi light-emitting diode (LED) optical probe (IMLOP) for intramural pacing of mouse hearts expressing cardiac-specific channelrhodopsin-2 (ChR2). Here we demonstrated that IMLOP insertion needs approximately 20 mN of force, limiting possible damage from excessive loads applied during implantation. Histological sections confirmed the confined nature of tissue damage during acute use. The temperature change of the surrounding tissue was below 1 K during LED operation, rendering the probe safe for use in situ . This was confirmed in control experiments where no effect on cardiac action potential conduction was observed even when using stimulation parameters twenty-fold greater than required for pacing. In situ experiments on ChR2-expressing mouse hearts demonstrated that optical stimulation is possible with light intensities as low as 700 μW/mm 2 ; although stable pacing requires higher intensities. When pacing with a single LED, rheobase and chronaxie values were 13.3 mW/mm2 ± 0.9 mW/mm 2 and 3 ms ± 0.6 ms, respectively. When doubling the stimulated volume the rheobase decreased significantly (6.5 mW/mm2 ± 0.9 mW/mm 2 ). We have demonstrated IMLOP-based intramural optical pacing of the heart. Probes cause locally constrained tissue damage in the acute setting and require low light intensities for pacing. Further development is necessary to assess effects of chronic implantation.